FACTORS AFFECTING BRAND LOYALTY OF PROMAG AND MYLANTA AMONG PHARMACY CUSTOMERS - Feni Febrianti Wibowo; Samsubar Saleh; Sampurno Sampurno (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Brand loyalty is an important concept among the competitive market of pharmaceutical industry. Strong brand loyalty willencourage customers to make a commitment on repeat buying and recommend that brand to others. The study aimed to analyze thefactors that affect consumer loyalty toward ulcer medicines, namely Promag and Mylanta.The study was a correlational study. Respondents were 200 pharmacy customers, divided into 100 customers who had been consumed Promag and 100 customers who had been consumed Mylanta. The research instrument used a questionnaire with Likert scale. Data wereanalyzed using multiple linear regression test.The results showed that the brand reputation, brand predictability, brand competence, trust in the company, and brand likingsimultaneously had a significant effect on both the brand loyalty of Promag (R2= 0,962) and Mylanta (R2= 0,931). To sum up, the brandreputation, brand predictability, brand competence, trust in the company, brand liking and loyalty of Promag were higher thanMylanta.Keywords: loyalty, Promag, Mylanta, brand